African Women Refugee Resettlement: A Womanist Analysis. (May 2016) - Haffejee, Badiah; East, Jean F.
In considering forced migration as a consequence of global conflict, women with refugee status are especially vulnerable. The influx of refugees into the United States, in this case, refugees from Africa, requires us to examine various aspects of what it means to be a refugee. Drawing upon current and extant literature, this article investigates the challenges faced by women refugees from Africa. A womanist framework is described and applied to four areas of resettlement experience including gendered expectations, trauma and mental health, economic self-sufficiency, and cultural integration. In addition, the policy assumptions of the Refugee Act of 1980 are contrasted with the realities and experiences of women refugees from Africa. Implications for social work practice, policy advocacy, and research are discussed.